Effect of palm oil mill final discharge on the physicochemical characteristics and bacterial community of river water - Tun Mohd Salim, Wan Nor Salmah (2015)
Palm oil industry plays a major role in Malaysia due to its contribution as a main exporter of palm oil throughout the world. Production of palm oil from fresh fruit bunch (FFB) involves several mechanical processes such as pressing, sterilizing and stripping which require large amount of water. However, huge water consumption leads to the formation of palm oil mill effluent (POME) and up to 50% of this wastewater will be discharged to the environment. Nowadays, most of the palm oil mills in Malaysia have been practicing the direct discharge of raw or partially treated POME into the river. This is due to the cheapest and easiest method for disposal since POME is a high strength wastewater and very difficult to manage. However, excessive amount of POME discharge will contribute to high organic content in the water stream. This condition needs high dissolved oxygen to be consumed by the microbes for degradation of organic matter. Thus, it will interrupt the environment of aquatic life. Besides, water pollution can cause serious health problems and potentially threaten both life quality and public health due to contamination of drinking water. Therefore, this study was carried out to investigate the physicochemical properties and bacterial community structure of the polluted river caused by palm oil mill final effluent in comparison to the unpolluted river. The water and sediment samples from Marong River, Negeri Sembilan, Malaysia which located near to the Felda Pasoh Hilir Palm Oil Mill were collected once a month started from November 2014 until January 2015. Seven physicochemical parameters were determined which were pH, temperature, biological oxygen demand (BOD), chemical oxygen demand (COD), total organic carbon (TOC), total suspended solid (TSS) and volatile suspended solid (VSS) by using standard methods. In addition, bacterial community structure was analyzed by denaturing gradient gel electrophoresis (DGGE) of PCR-amplified region of 16S rDNA from two different points of Marong River and palm oil mill final discharge. The upstream of Marong River was considered as unpolluted river as it was free from POME contamination, meanwhile the downstream and final discharge points were proposed as polluted river. From the results, the unpolluted river showed lower pH (6.38 - 7.13) compared to polluted river (7.27 - 8.27). Meanwhile the recorded temperature for both unpolluted and polluted river showed no significant difference, which was in the range of 26°C - 29°C. In addition, COD (31 mg/L - 107 mg/L), BOD (4.36 mg/L - 17.44 mg/L) and TOC (8.02 mg/L - 32.91 mg/L) of polluted river were higher compared to those of unpolluted river throughout three months sampling. The results showed similar characteristics profile with the sediment samples whereby the sediment in polluted river showed higher percentage of TOC which was in the range of 0.36% - 2.31% compared to the unpolluted river. Besides, the polluted river contained higher amount of TSS (53.33 mg/L - 70.00 mg/L) and VSS (33.33 mg/L - 66.67 mg/L) in comparison to unpolluted river. Based on the DGGE fingerprinting obtained, the changes of microbial community structure have been observed between polluted and unpolluted river. The study showed that shift in the bacterial community composition in the river water was affected by palm oil mill final discharge.